Synthesis of diesel additives from fructose over PWA/SBA-15 catalyst - Patil, Chetana R. (Fuel, 2018)
A series of composites of phosphotungstic acid (PWA) H3PW12O40 with SBA-15 were prepared by varying PWA amount from 5% to 30% by one-step sol-gel hydrothermal as well as by impregnation methods. Successful incorporation of PWA into the SBA-15 framework by sol-gel method was confirmed by 31P NMR in which a shifting of the peak due to tetrahedral ‘P’ atom of PWA from −14.32 and −14.49 ppm was observed. The composites exhibited both Brønsted and Lewis acidity, large and well distributed three dimensional interconnected pores with high surface areas exhibiting excellent activity for one pot synthesis of 5-(hydroxymethyl) furfural (5-HMF) and 5-(ethoxymethyl) furfural (EMF) from fructose. The minimum loading of 5% of PWA in SBA-15, gave 78% fructose conversion with the highest yield of 70% towards 5-HMF. Increase in PWA loading up to 20% resulted in the enhanced fructose conversion of 95% accompanied by further etherification of 5-HMF to 67 and 12% yield towards EMF and ethyl levulinate (EL), respectively. Increasing the % of PWA in SBA-15 matrix resulted in increase in the acidity of the composites giving the yield trend as 5-HMF < EMF < EL. Catalyst prepared by sol-gel method showed excellent recyclability up to 3 reuses
Keywords: 5-(Ethoxymethyl) furfural; 5-(Hydroxymethyl) furfural; Phosphotungstic acid; SBA-15